Strategi Pengembangan Usaha Mikro Kecil dan Menengah Arak Kopi di Desa Padang Sambian Kaja - I Kadek Jaya Perdana; I Gusti Ngurah Widya Hadi Saputra (JPPMI: Jurnal Pelayanan dan Pemberdayaan Masyarakat Indonesia, 2026)
Padangsambian Kaja Village is a village that has many MSMEs, one of which is the Arak Kopi UMKM, which until now has not been familiar with digital marketing, and only relies on conventional methods to attract consumers so that during the Covid - 19 pandemic like today, these MSMEs experienced a significant decrease in consumers. , this is due to the PSBB which urges the public to stay at home. The purpose of this Community Service Program is to provide an understanding of the importance of utilizing digital marketing as a promotional medium, especially during a pandemic. The methods of implementing this activity are observation, interview, education, and practice. And the result of this activity is to be able to provide solutions to problems experienced by Arak Kopi MEMEs related to the decline in consumers in the midst of a pandemic. It is hoped that this study report can be used as a guideline and input for similar service to be carried out in the future, namely by trying to introduce Digital Marketing to MSME players in other areas so that they are able to compete in the midst of the Pandemic and Globalization.